2014
DOI: 10.1542/peds.2013-3552
|View full text |Cite
|
Sign up to set email alerts
|

Baby-MONITOR: A Composite Indicator of NICU Quality

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The traditional processfocused approach to quality improvement has not remedied NICUs' inconsistency in quality of care delivery across clinically important measures. Global measurement of quality may induce broad, systems-based improvement, but must be formally studied. WHAT THIS STUDY ADDS:We present a systematically developed and robust composite indicator, the Baby-MONITOR, to assess the quality of care delivered to very low birth weight infants in the NICU setting. abstract BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 27 publications
0
75
0
4
Order By: Relevance
“…40 Although the optimal nutritional strategy for preterm infants is unknown, the high rates of postnatal growth failure and the wide variation in rates among NICUs suggest that quality improvement efforts related to nutritional management may have a role to play in improving nutritional support and growth for preterm infants. Using a Delphi process and expert panel, Profit et al 41 identified GV as 1 of 9 key measures included in the Baby-MONITOR, a composite indicator of NICU quality. Several quality improvement collaboratives have focused their efforts on improving nutrition and growth.…”
Section: Discussionmentioning
confidence: 99%
“…40 Although the optimal nutritional strategy for preterm infants is unknown, the high rates of postnatal growth failure and the wide variation in rates among NICUs suggest that quality improvement efforts related to nutritional management may have a role to play in improving nutritional support and growth for preterm infants. Using a Delphi process and expert panel, Profit et al 41 identified GV as 1 of 9 key measures included in the Baby-MONITOR, a composite indicator of NICU quality. Several quality improvement collaboratives have focused their efforts on improving nutrition and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Computation of Baby-MONITOR scores requires that its sub-components are aligned according to valence (higher score = better performance), risk adjusted, and standardized using the Draper-Gittoes method (12, 21). With this method, a standardized observed minus expected z score was computed, with an expected mean of zero and a standard deviation of one.…”
Section: Methodsmentioning
confidence: 99%
“…Although individual measures contain important information, there is also value in summarizing performance by combining the information from multiple measures, because such a summary can convey quality from many different perspectives (10). In prior work, we created a composite indicator, the Baby-MONITOR, as a comprehensive measure of the care and outcomes for VLBW infants (11, 12). In this paper, we used the Baby-MONITOR and its individual components to examine whether care and outcomes differ between different NICU levels.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we used the Baby-MONITOR composite indicator and its subcomponents (8). The Baby-MONITOR aggregates 9 risk-adjusted measures (2 process measures, 6 morbidities, and mortality) that span the birth hospitalization (911).…”
Section: Introductionmentioning
confidence: 99%